Analisis Perbandingan Rasio Keuangan Sektor Besi Baja 2019-2021 - Debby Shinta Wulan; Novita Rahmawati; Arys Arya Anfield; Cholis Hidayanti (Jurnal Akuntan Publik, 2024)
Indonesia's economy relies heavily on the steel industry, making it an important sector. This study was conducted with the aim of understanding the comparison of financial ratios. iron and steel sector in Indonesia in 2019 to 2021. This study utilizes secondary information derived from the annual financial statements of steel industry companies in Indonesia. The findings indicate an overall improvement in the financial performance of the steel sector in Indonesia in 2021 compared to 2019, as evidenced by an increase in most financial ratios. Therefore, the study concluded that the financial performance of the steel sector in Indonesia experienced positive growth in 2021. However, certain financial ratios, such as current ratio and quick ratio, still require careful attention.